2 SUBSTITUTED 4 2 DIALKYLAMINOETHYL THIAZOLES - SCHOLZC, R; MIZZONIR, H; DJERASSI, CARL (CIBA PHARMACEUTICAL PRODUCTS, RESEARCH DEPARTMENT DIVISION OF CHEMISTRY, SUMMIT, NJ, EUA, 1951)
1-Bromo-4-dialkylaminobutan-2-one hydrobromides, obtainable from the corresponding "Mannich bases", were condensed with (a) aryloxyacetothioamides to yield a series of 2-(aryloxymethyl)-4-(2-dialkylaminoethyl)thiazole dihydrobromides; (b) thioformamide, t
J REPROD FERTIL
Keywords: 2 SUBSTITUTED 4 2, DIALKYLAMINOETHYL THIAZOLES; QUIMICA; QUIMICA ORGANICA; RADICALES LIBRES